Olympian Myth and Gender Performitivity in Angela Carter’s The Passion of New Eve - Singh, Raj Kishor (Interdisciplinary Journal of Management and Social Sciences, 2021)
The Passion of New Eve is an Angela Carter’s critical response to the essentialism of the feminism of 1970s. People had assumption that female experience should be white, middle-class and heterosexual. This assumption has been distorted in the novel with the sense that, traditionally, gender is a social and cultural construct, and this has been illustrated in the story by showing how New Eve acquires womanhood through the socio-cultural situation in Zero’s harem and also while Eve is in love relationship with Tristessa. In her novel, Carter presents Evelyn as a model of gender transfer and acquisition. Greek myth and Carter’s myth have a good blending meta-narrative relationship, a mytho-grand-narrative. Mother is a good example of the Greek myth of Tiresias, a Hermaphrodite. Mother’s hermaphrodite body is used as a grotesque and Carnivalesque body similar to that of Tiresias. Evelyn feels horror at the grotesque and Carnivalesque, physical excesses of the body figure of Mother and expresses revulsion at the sight, but later he himself is turned into a mythic and monstrous being, like Greek god Androgynes, with both male and female physical and psychical features, and in case of Evelyn, with the body of a female but the mind of a man. Angela Carter presents a grotesque realism in the novel, and it is postmodernistic in characteristic because it subverts the patriarchal myths of femininity and masculinity and makes a strong debatable argument over essentializing and universalizing tendencies in the feminism of the 1970s, with the allusions to Greek myths and the biblical story of Adam and Eve. The novel confirms de Beauvoir’s theory that one is not born but rather becomes a woman. Through New Eve, we learn the postmodernistic fact raised by the feminists that biological sex and culturally determined gendered one are not the same, but two different things.